Analyzing Factors That Affect Purchasing Decisions For Beauty Products Through Tiktok Review Videos - Athaya, Neysa Shifra; Wandebori, Harimukti (Integrasi Sains Media, 2024)
The rise of social media, particularly TikTok, has significantly influenced consumer behaviour in the beauty product industry, especially among Generation Z in Indonesia. With millions of active users, TikTok has become a powerful platform for beauty enthusiasts and influencers to share product reviews, tips, and recommendations. This research aims to analyze the key factors influencing purchasing decisions for beauty products through TikTok video reviews. The primary factors identified include perceived credibility, perceived authenticity, review quality, and review quantity. This study also examines the relationship between these factors and purchase intentions and how they ultimately influence purchase decisions. A quantitative approach was used for this research, implementing non-probability and judgmental sampling techniques. An online questionnaire was distributed to 239 respondents aged 15 to 24 living in Indonesia, targeting individuals who actively engage with beauty product reviews on TikTok. The data were analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that perceived credibility, perceived authenticity, review quality, and review quantity positively and significantly affect purchase intentions. Additionally, purchase intentions were shown to directly impact purchase decisions without being moderated by the attitude of others or unanticipated situational factors. The research also identified three consumer needs-based segments, namely quality-based, price-based, and ingredient-based. Each segment reflects different priorities and behaviours in response to beauty product reviews on TikTok. The findings will give insight into how beauty brands can enhance their marketing strategies on TikTok. By focusing on improving the perceived credibility, authenticity, review quality, and review quantity of their TikTok review videos, marketers can effectively influence consumer purchase intentions and decisions. These strategies can help beauty brands maximize sales and ensure long-term sustainability in the competitive market.